Using instant messaging applications to promote clinical teaching of medical students - Mohammadreza Saeedbakhsh; Athar Omid; Mahsa Khodadoostan; Ahmad Shavakhi; Peyman Adibi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The main purpose of this study was to evaluate the use of Telegram as an Instant messaging application in clinical teaching of medical students, especially clinical ward rounds. MATERIALS AND METHODS: In this quasi-experimental study, Telegram as an Instant messaging application was employed. To do this, a Telegram group entitled as "Lavender" was created and then selected patients were divided between students and externs daily. After that, students and externs were asked to take medical histories, perform complete physical examinations, and then share their data in the Lavender group. Ultimately, to evaluate the effects of this intervention, two quantitative and qualitative approaches were used. RESULTS: From the students' point of view the highest average was associated with "Readiness for teaching round" (3.71 ± 1.34) and the lowest average was related to "Time-saving for studying about illnesses" (2.08 ± 1.44). In addition, medical trainees mentioned that reporting patients' daily medical histories and progress notes could create a reflective process. The suggestion made by many medical trainees was to select and discuss simpler cases who have more teaching points for them, while other trainees recommended focusing on common illnesses in the Lavender group. CONCLUSION: The use of messaging software applications such as Telegram in medical education has created a new paradigm, which could facilitate interpersonal interactions among trainees.